Predatory-Prey Decision Making During Market Bubbles—Preliminary Evidence from a Neurobiological Study. Issue 3 (2nd July 2016) - Mesly, Olivier; Bouchard, Stéphane
ABSTRACT: The present paper examines decision making during market bubbles. In the context of high market volatility, high speculation and inappropriate regulation (e.g., as such was the case in the years prior to the 2008 subprime crisis), market agents adopt either a predator or prey position. By way of a neurobiological study, it is shown that market-agent-turned preys benefit from moderate stress when it enhances their level of vigilance; however, past a certain stress threshold, their efforts at wealth maximization are considerably reduced. This may explain some of the cognitive causes of failures found by various authors in their description of the market bubble phenomenon. The paper emphasizes the importance of setting up proper regulations aimed at preventing the emergence of predatory behaviors (such as those that prevailed with the establishment of predatory mortgages during the year 2000 in the United States) and better educating average investors.